Al-Ghazâlî dan Pengaruhnya terhadap Perkembangan Dunia Islam - Dwi Runjani Juwita (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Al-Ghazâlî was a famous islamic intellectual both in western world and eastern world. He’s a leader who has a name h?ujjat al-islâm, its mean a great figure of islamic development cause of his thoughts. He was a great thinker and very productive in the islam world. A long his life dedicated to the advancement of science. His works adorn the thinkers of his era and after. His writings were about many diciplines. Some of his great works were Ih?yâ ‘Ulûm al-Dîn and al-Munqid Min al-Z?alâl.